Analysis of student ability formulating learning objectives in natural science phase D kurikulum merdeka - Darmanella Dian Eka Wati; Ratih Komala Dewi; Chairul Amri (Universitas Negeri Padang, 2023)
Prospective Biology teachers must have the ability to formulate learning objectives to develop teaching modules for science subjects according to kurikulum merdeka. Therefore, the research was conducted to measure students' ability to formulate learning objectives, especially for phase D. This research is a descriptive-qualitative, which begins with the preparation of indicators for assessing abilities, validating assessment indicators, collecting work results, processing and analyzing data, data tabulation, and discuss it descriptively. Based on the results of the study, 80% of students were very good at formulating learning objectives, 7% of students were in the good category, 7% of students were in the sufficient category, and the rest were in the less category. It was concluded that most of the students had a very good ability to formulate learning objectives, for the biology subject of Science in Phase D.